Antimalarial activity of ruthenium(ii) and osmium(ii) arene complexes with mono- and bidentate chloroquine analogue ligands. Issue 44 (22nd October 2015) - Ekengard, Erik; Glans, Lotta; Cassells, Irwin; Fogeron, Thibault; Govender, Preshendren; Stringer, Tameryn; Chellan, Prinessa; Lisensky, George C.; Hersh, William H.; Doverbratt, Isa; Lidin, Sven; de Kock, Carmen; et al.
Abstract : Thirteen new ruthenium and osmium half-sandwich complexes with chloroquine analogue ligands have been synthesized and evaluated for anti-malarial properties. Abstract : Eight new ruthenium and five new osmium p -cymene half-sandwich complexes have been synthesized, characterized and evaluated for antimalarial activity. All complexes contain ligands that are based on a 4-chloroquinoline framework related to the antimalarial drug chloroquine. LigandsHL 1–8 are salicylaldimine derivatives, whereHL 1 = N -(2-((2-hydroxyphenyl)methylimino)ethyl)-7-chloroquinolin-4-amine, andHL 2–8 contain non-hydrogen substituents in the 3-position of the salicylaldimine ring, viz . F, Cl, Br, I, NO2, OMe and t Bu forHL 2–8, respectively. LigandHL 9 is also a salicylaldimine-containing ligand with substitutions in both 3- and 5-positions of the salicylaldimine moiety, i.e. N -(2-((2-hydroxy-3, 5-di- tert -butylphenyl)methyl-imino)ethyl)-7-chloroquinolin-4-amine, whileHL 10 is N -(2-((1-methyl- 1H -imidazol-2-yl)methylamino)ethyl)-7-chloroquinolin-4-amine) The half sandwich metal complexes that have been investigated are [Ru(η 6 -cym)(L 1–8 )Cl] (Ru-1 –Ru-8, cym = p -cymene), [Os(η 6 -cym)(L 1–3, 5, 7 )Cl] (Os-1 –Os-3, Os-5, and Os-7 ), [M(η 6 -cym)(HL 9 )Cl2 ] (M = Ru, Ru-HL 9 ; M = Os, Os-HL 9 ) and [M(η 6 -cym)(L 10 )Cl]Cl (M = Ru, Ru-10 ; M = Os, Os-10 ). In complexes Ru-1 –Ru-8 and Ru-10, Os-1 –Os-3, Os-5 and Os-7 and Os-10, the ligands were found to coordinate as bidentate N, O - and N, N -chelates, while in complexes Ru-HL 9 and Os-HL 9, monodentate coordination of the ligands through the quinoline nitrogen was established. The antimalarial activity of the new ligands and complexes was evaluated against chloroquine sensitive (NF54 and D10) and chloroquine resistant (Dd2) Plasmodium falciparum malaria parasite strains. Coordination of ruthenium and osmium arene moieties to the ligands resulted in lower antiplasmodial activities relative to the free ligands, but the resistance index is better for the ruthenium complexes compared to chloroquine. Overall, osmium complexes appeared to be less active than the corresponding ruthenium complexes.